How Organizational Change Affects Lecturers' Innovative Learning Through The Moderating Openness To Experience - Zarkasyi, Ahmad; Kausar, Shakila (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Changes in the form of higher education are not only about departmental restructuring, but also about the university's role in managing human resources, organizational culture, and its openness to new experiences and methods. This study examines the effect of organizational change on lecturers' learning innovation, with a focus on the moderating role of openness to experience, in three private universities in East Java Province. The survey design used in this study is quantitative and non-experimental. Purposive sampling was used to choose 151 academics in total to take part in this survey study. The collected data were then analysed using the SmartPLS 4.0 application and the IBM Statistical Package for the Social Sciences (SPSS) version 23 for descriptive analysis of the frequency of respondents' answers. The results of the SMART-PLS 4.0 research showed that 1) organizational change had a 77.3% impact on openness to experience. 2) Learning innovation was 48.0% impacted by organizational change. 3) Learning innovation is impacted by openness to experience by 40.6%. Organizational change increases receptivity to experience, which has a 13.5% impact on learning innovation. The study's findings should motivate instructors to share more information, thereby enhancing their own capacity for innovation and positively impacting student achievement in higher education.